GSTO1-1 plays a pro-inflammatory role in models of inflammation, colitis and obesity - O'NEILL, LUKE (My University, 2017)
Glutathione transferase Omega 1 (GSTO1-1) is an atypical GST reported to play a pro-inflammatory role in response to LPS. Here we show that genetic knockout of Gsto1 alters the response of mice to three distinct inflammatory disease models. GSTO1-1 deficiency ameliorates the inflammatory response stimulated by LPS and attenuates the inflammatory impact of a high fat diet on glucose tolerance and insulin resistance. In contrast, GSTO1-1 deficient mice show a more severe inflammatory response and increased escape of bacteria from the colon into the lymphatic system in a dextran sodium sulfate mediated model of inflammatory bowel disease. These responses are similar to those of TLR4 and MyD88 deficient mice in these models and confirm that GSTO1-1 is critical for a TLR4-like pro-inflammatory response in vivo . In wild-type mice, we show that a small molecule inhibitor that covalently binds in the active site of GSTO1-1 can be used to ameliorate the inflammatory response to LPS. Our findings demonstrate the potential therapeutic utility of GSTO1-1 inhibitors in the modulation of inflammation and suggest their possible application in the treatment of a range of inflammatory conditions.
Keywords: Glutathione transferase Omega 1 (GSTO1-1)